2016
DOI: 10.1016/j.atherosclerosis.2016.07.599
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoproteins exert pro-inflammatory effects on macrophages via passive cholesterol depletion and PKC-NF-kb/stat1-irf1 signaling

Abstract: Background: Membrane cholesterol is known to modulate a variety of cell signaling pathways and functions. While cholesterol depletion by High-Density Lipoproteins (HDL) has potent antiinflammatory effects in various cell types, its effect on inflammatory responses in macrophages remain ill defined. Methods & Results: Pre-incubation of human and murine macrophages in vitro with human reconstituted (apolipoproteinA-I/phosphatidylcholine) or native HDL significantly decreased LPS-induced anti-inflammatory IL-10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, this study reported antiinflammatory effects of native HDL, although these experiments were performed in TLR4 mutant C3H/HeJ mice, which display a defective response to bacterial endotoxins like LPS. In contrast, we recently showed clear pro-inflammatory effects of HDL on macrophages using physiological concentrations of both native HDL and 1-palmitoyl-2-linoleoyl-phosphatidylcholine apoA-I reconstituted HDL in (macrophages from) C57Bl/6 mice [12].…”
mentioning
confidence: 78%
“…In addition, this study reported antiinflammatory effects of native HDL, although these experiments were performed in TLR4 mutant C3H/HeJ mice, which display a defective response to bacterial endotoxins like LPS. In contrast, we recently showed clear pro-inflammatory effects of HDL on macrophages using physiological concentrations of both native HDL and 1-palmitoyl-2-linoleoyl-phosphatidylcholine apoA-I reconstituted HDL in (macrophages from) C57Bl/6 mice [12].…”
mentioning
confidence: 78%
“…Therefore, ATF3, which acts as a negative transcription factor, inhibits the induction of cytokines in the presence of TLR stimuli (305). In contrast to the antiinflammatory effects of HDL, a recent study indicated a pro-inflammatory effect of HDL on macrophages via passive cholesterol depletion highlightening the complexity of HDL functionality (306).…”
Section: The Immunomodulatory Effects Of Hdlmentioning
confidence: 99%